Family Strategy in Giving Antipsychotic Medications to Family Members with Mental Disorders - Jovanka, Indryani (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2023)
Introduction: Recurrence in people with mental disorders is often due to medication withdrawal. The primary supporter of giving medications at home is the family. The purpose of this study was to identify the family strategy for treating family members who have mental disorders with antipsychotic medications.Method: The method used in this study is survey-based descriptive quantitative research with 100 samples that are representative of families with mental disorders and using accidental sampling technique. The inclusion criteria were family accompanying them with mental disorders control to a mental hospital who had difficulty taking medicine. The researcher's questionnaire is based on a literature review. The analysis and presenting of data use frequency distribution.Results: The survey showed that the strategy most often used was to involve patients in the decision to get medicine (100%). The most frequently successful families were to understand patients' importance and remind them when to take medicine (93%), but most often, it didn't work. Instead, what is done is to involve the patient in the decision to get the medications (16%), and the most that has never been done is to change the oral to injection medication (65%).Conclusions: A family responsibility to reduce the rate of recurrence should be to remind the patient to take their medications.